2018
DOI: 10.3390/molecules24010115
|View full text |Cite
|
Sign up to set email alerts
|

Basic Study of Drug-Drug Interaction between Memantine and the Traditional Japanese Kampo Medicine Yokukansan

Abstract: Several basic pharmacokinetic and pharmacological studies were conducted as part of a group of studies to clarify the drug-drug interaction (DDI) between memantine (MEM), a drug used to treat Alzheimer’s disease, and yokukansan (YKS), a traditional Japanese Kampo medicine used to treat behavioral and psychological symptoms of dementia. The pharmacokinetic studies showed that there were no statistically significant differences in MEM concentrations in the plasma, brain, and urine between mice treated with MEM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Gai et al (2014) detected GM and its metabolite 18-hydroxy-GM in 8 h urine samples from mice orally administered YGS (9.1 g/kg). Matsumoto et al (2018) detected GM in urine samples collected during 24 h from mice orally administered YKS (1 g/kg) in a basic study of drug-drug interactions between memantine and YKS. Furthermore, Gai et al (2014) confirmed the urinary excretion of CX, ICX, RP, IRP, HTE, 11-hydroxy HTE, and 19-carbonyl HTI in addition to GM in mice orally treated with YGS.…”
Section: Urinary Excretionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gai et al (2014) detected GM and its metabolite 18-hydroxy-GM in 8 h urine samples from mice orally administered YGS (9.1 g/kg). Matsumoto et al (2018) detected GM in urine samples collected during 24 h from mice orally administered YKS (1 g/kg) in a basic study of drug-drug interactions between memantine and YKS. Furthermore, Gai et al (2014) confirmed the urinary excretion of CX, ICX, RP, IRP, HTE, 11-hydroxy HTE, and 19-carbonyl HTI in addition to GM in mice orally treated with YGS.…”
Section: Urinary Excretionmentioning
confidence: 99%
“…Most pharmacokinetic studies of GM have been performed after the oral administration of crude drug products (Kushida et al, 2013;Matsumoto et al, 2018;Takiyama, et al, 2019) (Table 2). Although the absolute bioavailability of GM has not been verified, many studies revealed that GM in the intestinal lumen following oral administration is certainly absorbed into portal vein blood and transferred to circulating blood.…”
Section: Administration Of Uh-containing Crude Drug Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parts of the crude drugs used in the Kampo formulas are also used in health foods and supplements. Kampo formulas have traditionally been prescribed for a number of health conditions, including chronic hepatitis, bronchial asthma, allergic rhinitis, anemia, and gastric cancer, and gradually reemerged in Japan as alternatives to Western medicine [23,24,25,26,27,28]. In a recent survey, approximately 90% of Japanese doctors prescribe Kampo formulas in their daily medical practice [29].…”
Section: Introductionmentioning
confidence: 99%